Presentation of Childhood Squint - Shah, Mir Ali; Khan, Saleem; Muhammad, Shad (Journal of Postgraduate Medical Institute, 2011)
this is a prospective study of fifty consecutive cases of squint in Children. The study was designed to find out the age of onset and presentation of childhood squint along with the influence of heriditory and refractive errors. The study was conducted from November 1994 to August 1996 at the department of Ophthalmology, LRH Peshawar. Inquires regarding history of state of vision, duration of deviation laterality, head tilt, fever trauma, consanguinity, refractive error or squint in family, drugs taken during pregnancy, smoking and antenatal problems, were made. full ophthalmic examiantion, cycloplegic retinoscopy and fundoscopy and tests for binocular single vision were performed and amblyopia noted. of these 50 patients, 54% were males and 46% were females with an age range between 6 months and 16 years. Esotropia was seen in 74% of patients and myopia in only 6% whereas 20% of patients were emmetrope. 32% of children were ambloypic and consanguinity was present in 62%. the presentation was the most common type Anisometropic strabismus was found to be a common cause of ambloyopia and heredity has an influence on childhood squint.